Development of portable desk for biomechanics equipment - Shahren, Abd Manap (2013)
The objective of this project is to design and fabricate a portable desk and camera stand. Portable desk main function is it can place the biomechanics equipment into it. Besides that, it can place the desktop so that the high speed camera can be attach into it during outdoor session. For the camera stand, it mainly function is to attach the high speed camera from top view. Tripod camera that have been sell in market can be a camera stand that can take a picture from bottom and front view. The material that have been used to fabricating the portable desk is mild steel while material used to fabricating the camera stand is aluminum. The portable desk have wheel so that the portable desk can be brought anywhere easily. The process that involved to fabricating both portable desk and camera stand is welding, drilling, grinding, cutting and riveting. There are also several problems faced during the fabrication process. Material selection was one of the biggest problems. In order to find the most suitable raw material for the portable desk and camera stand, research and information are searched through reliable source. Wrong selection of material will cause a lot of difficulties during fabrication process and will lead to more trouble in the future. The problem is counter by make some research from the internet and book. Lastly, the objective of this project has been achieved where the portable desk can been brought anywhere easily while the camera stand can been used to attach the high speed camera into it. The experiment can be conducted during outdoor session.